2020
DOI: 10.1186/s12969-020-00459-0
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease with a concomitant primary Epstein - Barr virus infection

Abstract: Background: Kwasaki disease (KD) is the leading cause of acquired heart disease in children in most developed countries. The cause of KD remains unknown. The presumed theory is that KD occurs due to one or more infectious agents who evoke an abnormal immunological response in susceptible individuals. Epstein-Barr virus (EBV) infection has been considered as a suspected causative agent because of the potential effect on the immune system. Case presentation: A previously healthy 19 month old boy presented with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
8
0
6
Order By: Relevance
“…It has been associated with a variety of infectious diseases and involved in the removal of virus such as varicella zoster and Epstein-Barr virus (EBV). One case report demonstrated that EBV infection could be considered as a suspected causative agent because of the potential effect on the immune system in KD [ 27 ]. GZMB represents a serine proteinase and plays a central role in killing human tumor cell lines, which can induce cell death, apoptosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with a variety of infectious diseases and involved in the removal of virus such as varicella zoster and Epstein-Barr virus (EBV). One case report demonstrated that EBV infection could be considered as a suspected causative agent because of the potential effect on the immune system in KD [ 27 ]. GZMB represents a serine proteinase and plays a central role in killing human tumor cell lines, which can induce cell death, apoptosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, both viruses could be associated with KD in children under the age of 5, because most adolescents and adults have developed protective immunity on EBV and CMV. [ 10 11 12 ] In addition, HIV is the most frequently reported infectious disease associated with KD in adults' rare cases. [ 12 ] Although MIS-C has overlapping features with KD, our patients with MIS-C were adolescents with frequent gastrointestinal and cardiovascular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Более 80% случаев заболевания приходится на возраст от 6 месяцев до 4 лет. Низкая частота БК в течение первых 6 месяцев свидетельствует об иммунитете, обусловленном материнскими антителами [25]. Инфекционные агенты, которые связаны с БК, включают такие бактерии, как Propionibacterium, Staphylococcus aureus, Streptococcus pyogenes и Chlamydia, а также вирусы, такие как ВЭБ, парвовирус В19, ретровирус и другие.…”
Section:  ранние осложненияunclassified
“…Инфекционные агенты, которые связаны с БК, включают такие бактерии, как Propionibacterium, Staphylococcus aureus, Streptococcus pyogenes и Chlamydia, а также вирусы, такие как ВЭБ, парвовирус В19, ретровирус и другие. Генетическая значимость в патогенезе БК подчеркивается тем фактом, что существует более высокий риск у детей из Северо-Восточной Азии, братьев, сестер и детей, переболевших БК в анамнезе [25]. Одна из теорий предполагает, что инфекционные агенты вызывают неадекватный иммунологический ответ на антиген у генетически восприимчивых индивидуумов [25].…”
Section:  ранние осложненияunclassified